Peran Desa Sebagai Basis Migrasi Aman dalam Perlindungan Tenaga Kerja Indonesia - Riris Ardhanariswari; Kadar Pamuji; Oktafiani Catur P. (Faculty of Law, Universitas Pekalongan, 2017)
The lack of knowledge possessed by Indonesian labor abroad gives rise to some vulnerability. An urgent problem to solve is the formulation of village regu-lations on the protection of the Pamijen Village workforce in order for Indonesian workers from Pamijen Village to be protected for safe migration and to ensure that abandoned families can educate abandoned children well. This research uses a qualitative approach because it has advantages in constructing social reality, cultural meaning, focusing on interactive processes and events. The authors discussed with Pamijen Village Government to get inputs related to improving the capacity of the village apparatus through training on the formulation of Village Regulations on the Protection of Indonesian Workers and then conducting public hearing activities through focus group discussions. The results of the research conducted in Pamijen Village, Sokaraja Sub-district resulted in an agreement to draft the Pamijen Village Rule of Re-gulation on the Protection of Prospective Indonesian Workers/ Indonesian Migrant Workers and Their FamiliesKeywords: Village, Protection, Indonesian Worker